2020
DOI: 10.1093/pcp/pcaa057
|View full text |Cite
|
Sign up to set email alerts
|

A Genome-Wide Association Study for Resistance to the Insect Pest Leptocybe invasa in Eucalyptus grandis Reveals Genomic Regions and Positional Candidate Defense Genes

Abstract: The galling insect, Leptocybe invasa, causes significant losses in plantations of various Eucalyptus species and hybrids, threatening its economic viability. We applied a Genome-Wide Association Study (GWAS) to identify single nucleotide polymorphism (SNP) markers associated with resistance to L. invasa. A total of 563 insect-challenged Eucalyptus grandis trees, from 61 half-sib families, were genotyped using the EUChip60K SNP chip and we identified 15,445 informative SNP markers in the test population. Multi-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…A recent genome-wide association study in an E. grandis breeding population identified candidate genomic regions on chromosomes 3, 7, and 8 that contained putative candidate genes for tolerance. These candidate genomic regions explained ∼17.6% of the total phenotypic variation of L. invasa tolerance (Mhoswa et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A recent genome-wide association study in an E. grandis breeding population identified candidate genomic regions on chromosomes 3, 7, and 8 that contained putative candidate genes for tolerance. These candidate genomic regions explained ∼17.6% of the total phenotypic variation of L. invasa tolerance (Mhoswa et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…To date, however, most studies have been limited to investigating the susceptibility of a particular genotype by counting the number of galls grown on plants in both nurseries and fields. It has recently been suggested that metabolites 21,23–27 and genes 28,29 may participate in this interaction, but such studies could not clarify whether the plant genotype affected the development time of the different gall stages. Based on the results of these studies, it remains not possible to determine the stages of gall development or the biological cycle of the insect when the defense mechanisms of each plant genotype are the most active.…”
Section: Introductionmentioning
confidence: 99%
“…The foliar fungal communities of 179 individual trees (0, n = 49; 1, n = 50; 2, n = 56; 3, n = 24) were analysed. The Eucalyptus population was analysed and genotyped in previous studies ( Naidoo et al, 2018 ; Mhoswa et al, 2020 ) and DNA extracts from those studies were used. Importantly, DNA was extracted from non-surface sterilised leaf punches of non-symptomatic leaf tissues and care was taken to avoid the galled areas of the leaves; thus, non-symptomatic tissue was used for all DNA samples.…”
Section: Methodsmentioning
confidence: 99%
“…Eucalyptus plantations are of high economic value globally ( Wingfield et al, 2015 ). In recent years, their yield has been jeopardised by the gall-forming wasp Leptocybe invasa Fisher and LaSalle (Hymenoptera: Eulophidae), which deposits eggs into new growth of Eucalyptus trees ( Naidoo et al, 2011 ; Dittrich-Schröder et al, 2018 ; Mhoswa et al, 2020 ). A high density of L .…”
Section: Introductionmentioning
confidence: 99%